Multilayered coated infra-red surface plasmon resonance fibre sensors for chemical sensing - Kalli, Kyriacos; Webb, David J.; Allsop, Thomas P.; Neal, Ron M.; Mou, Chengbo; Brown, Patrick R.; Rehman, Saeed Ur; Mapps, Desmond J.; Bennion, Ian (My University, 2009)
In this paper we report on the sensing potential of these infra-red SPR fibre devices using various metal overlay coatings and compare the performance of these sensors to a long period grating sensor. This comparison shows that the SPR fibre sensors out-perform the LPG sensor in the low and aqueous index regime.
Keywords: Fiber optics; Bragg gratings; Optical fibers